Perception of Social Maturity Criteria, Self-perception and Value Orientations among Russian Millennials - Alexander M. Rikel (Peoples' Friendship University of Russia (RUDN University), 2020)
The difference between generations is becoming increasingly apparent in the modern world. These days, one can observe over and over again how the intergenerational transmission of values is violated, and the differences between generations are becoming more and more noticeable. A number of studies are focused on the features that distinguish modern generations from each other, the values of generations as well as the perception of these values both by a particular generation and members of cohorts interacting with it. Some researchers note that the modern young generation (the so-called 'Generation Y', 'Gen Y' or 'millennials'), in comparison with their parents (the so-called 'Generation X', 'Gen X'), is characterised by a rejection of previously accepted criteria for social maturity (which can be understood as compliance with a number of social-psychological standards). However, there are practically no studies addressing this topic. The article describes a quantitative and qualitative study conducted in three stages, which involved 349, 25 and 100 subjects respectively. At the first stage, the data of the Russian longitudinal monitoring survey (RLMS) of households conducted by HSE University were used and analysed; at the second stage, a series of semi-structured interviews was conducted on the topic of perception of social maturity; at the third stage, the values of generational cohorts were investigated using the Rokeach Value Survey (RVS) and the author's questionnaire, which makes it possible to assess the influence of the cultural context on the formation of values. Within the first (auxiliary) stage, the basic hypothesis was confirmed about the differences in the compliance with the social maturity criteria (age of marriage, presence of children in the family, financial independence) among the young (Y) and older (X) generations of modern Russians. As part of the second stage, the features of the perception of these differences were identified. And at the third stage, it was proposed to interpret the differences using the values identified in millennials and the features of the perception of these values by themselves and Gen Xers.